Impact of treated sewage effluent on soil fertility, salinization, and heavy metal content - Silva Barbosa, Aline Michelle da [UNESP]; Faria, Rogerio Teixeira de [UNESP]; Saran, Luciana Maria [UNESP]; Santos, Gilmar Oliveira [UNESP]; Dantas, Geffson de Figueiredo [UNESP]; Coelho, Anderson Prates [UNESP] (Inst Agronomico, 2021)
A long-term experiment (2013 to 2017) of treated sewage effluent (TSE) levels via fertigation in a humid tropical region was installed in Jaboticabal, state of Sao Paulo, Southeast of Brazil, to evaluate the impact of TSE on soil fertility and the potential for salinization and heavy metal contamination of an Oxisol. The area was cultivated with Urochloa brizantha under the application of four TSE levels at the irrigation depth (0, 11, 60, and 100% TSE) during the four years of the experiment. The TSE chemical composition was monitored throughout the experimental period. The heavy metal levels and soil fertility were evaluated in the 0-0.10 and 0.10-0.20 m layers at the end of the four years of the experiment. Fertigation using TSE did not increase the concentration of potentially toxic elements (As, Cd, Cu, Hg, Mo, Ni, Pb, Se, and Zn) in the soil due to their low concentration in the effluent. A higher Na concentration was also observed at high TSE levels (60 and 100%). However, the sodium adsorption rate in the TSE was low, generating no potential for soil salinization and sodification. Fertigation with TSE levels increased soil fertility, increasing by more than 10% the P content and base saturation in the soil compared to control. According to the chemical attributes evaluated in the soil and effluent, this long-term study showed that TSE application via fertigation in humid tropical regions on clayey soils cultivated with forage grasses is recommended.
Keywords: water reuse; environmental contamination; soil chemical analysis; potentially toxic elements; wastewater